OCCUPATIONAL-RELATED INJURIES OF THE PERIPHERAL NERVOUS SYSTEM IN MECHANICAL ENGINEERING WORKERS IN NORTHERN BULGARIA - Irena Y. Stoilova; Radostina P. Madjarova; Vanya A. Birdanova (Peytchinski Publishing, 2021)
Mechanical engineering is traditionally well developed in Northern Bulgaria. With the development of production and technical progress, some health problems for workers appear. The aim of this study was to examine the damage of the peripheral nervous system in workers in mechanical engineering and to propose measures for the prevention of accidents and occupational diseases. Subjects of the study are 65 persons employed in mechanical engineering. Conclusions are made and recommendations given for improvement of the work conditions and organization of the work.